Sovereign bankruptcy - Pikuleva, Irina (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
The concept of sovereign bankruptcy originated in the works of A. Smith, B. Miller, in which the need for the formation of the mechanism of bankruptcy of public law entities was anyhow pointed and justified in order to optimize the economic climates in the countries during the crisis, to keep the state competitiveness in the global stage and the overstability of economic processes at both the national and international levels. The concerned problematics is anxiously actual in light of the recent events: the escalation of military conflicts, geopolitical tensions in the international community, hyperinflation, raising US government debt, etc. The factual financial insolvency of a number of states becomes a major problem. The resolution of this issue requires not only formation of the institution of the state bankruptcy at a theoretical level, but also effective procedures which will be able to cope with a debt crisis of public legal entities in practice. An attempt to present the history of the idea of sovereign bankruptcy, to systematize the most appropriate mechanisms and suggested ways of overcoming the debt crisis in the area of sovereign insolvency was made by the author. The problem of bankruptcy of administrativeterritorial units was indicated separately